10x-3=63

Simple and best practice solution for 10x-3=63 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10x-3=63 equation:


Simplifying
10x + -3 = 63

Reorder the terms:
-3 + 10x = 63

Solving
-3 + 10x = 63

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 10x = 63 + 3

Combine like terms: -3 + 3 = 0
0 + 10x = 63 + 3
10x = 63 + 3

Combine like terms: 63 + 3 = 66
10x = 66

Divide each side by '10'.
x = 6.6

Simplifying
x = 6.6

See similar equations:

| 4+4=y | | 9x+5y=45 | | x+x-4=0 | | w/4+5/8-2w/2=7/8-2w/4 | | x+y+2x=0 | | 3f+5=8 | | 5r-9(r-8)-20+2r= | | X-(5-3x)=7x+5 | | M^2+14m+13=0 | | 6r-9(r+8)+30+2r= | | 1.67+.67x=2.17+3.5x+.5 | | 10=x-8+8x | | 80=8x+10 | | 18x^3+39x^2+18x= | | Y=1.5x+7 | | 6x+-7-(2x)+4-5x+13= | | -5-7= | | 6x+-7-(2x)+4-5x+13=0 | | 8x-7y=14 | | x-10=-6x-10 | | 8/3=d/21 | | 2a^2+11ab+5b^2= | | 3t+(-6t)+5=29 | | 2x+27+x=180 | | (2x+-1)(x+8)=0 | | (-w+6)(3w-6)=0 | | -4(x+3)=8 | | 2x+x+22=x+38 | | 6=x-4.5 | | 2x^2=240 | | (v-4)(v-1)=0 | | 12/52=z |

Equations solver categories